Use of engineered landfills for arctic mine site reclamation - Johnson, D (Mine Closure 2011: Proceedings of the Sixth International Conference on Mine Closure, 2011)
One of the objectives of any mine site reclamation should be to minimise long-term environmental risk. Tailings and waste rock are typically the most problematic wastes generated during mining that must be addressed during closure. However, mine site reclamation generates many other types of solid waste including; hazardous waste, contaminated soil, and demolition debris. Hazardous waste such as fuel and process chemicals can be packaged and transported off-site for treatment and disposal at licensed facilities. However, demolition debris may have to be managed on-site because transportation of recyclable materials to market may not be economic. At remote mine sites, construction of an engineered landfill to manage solid non-hazardous waste may be required to minimise long-term risk to human health, wildlife and water quality. Design and operation of a solid waste landfill in an arctic climate presents some unique challenges. Recognising the short construction season in the arctic, it is important to not only carefully plan the site reclamation program but also have a technically suitable landfill design that can be constructed, filled and closed quickly. Depending on the size of the mine site and projected volume of solid waste requiring disposal in a landfill, it may be necessary to complete some foundation preparation and construction material stockpiling in advance of landfill construction. Siting options at a closed mine site that can be considered for construction of an engineered landfill include; open pit mine excavations, quarries, borrow areas, tailings areas, waste rock dumps, and natural topographic containment. If permafrost is present, it may be utilised to either create an impermeable liner or encapsulate the waste in ice. Finally after construction, annual post-closure geotechnical inspections should be carried out to demonstrate that the landfill is physically stable. Two case studies will be presented where engineered landfills were constructed and utilised for onsite disposal of solid waste generated during mine site reclamation in the Canadian Arctic.